2013
DOI: 10.1038/nature12332
|View full text |Cite
|
Sign up to set email alerts
|

Non-vesicular trafficking by a ceramide-1-phosphate transfer protein regulates eicosanoids

Abstract: Phosphorylated sphingolipids [ceramide-1-phosphate (C1P) and sphingosine-1-phosphate (S1P)] have emerged as key regulators of cell growth, survival, migration, and inflammation1–5. C1P (Fig. 1a) produced by ceramide kinase is an activator of group IVA cytosolic phospholipase A2α (cPLA2α), the rate-limiting releaser of arachidonic acid used for pro-inflammatory eicosanoid production3,6–9, which contributes to disease pathogenesis in asthma/airway hyper-responsiveness, cancer, atherosclerosis, and thrombosis. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
264
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(284 citation statements)
references
References 34 publications
20
264
0
Order By: Relevance
“…The structural data are consistent with a cleft-like conformational gating mechanism, whereby glycolipid chains sequentially enter and leave the molded-to-fit hydrophobic tunnel in the membrane-associated state during membrane vesicle biogenesis and trafficking (21).…”
Section: Expanding Horizonssupporting
confidence: 63%
“…The structural data are consistent with a cleft-like conformational gating mechanism, whereby glycolipid chains sequentially enter and leave the molded-to-fit hydrophobic tunnel in the membrane-associated state during membrane vesicle biogenesis and trafficking (21).…”
Section: Expanding Horizonssupporting
confidence: 63%
“…Recent studies have shown that sphingolipids are synthesized through the membrane-trafficking system and transported across membranes by various mechanisms (9)(10)(11). Many single-celled eukaryotes (i.e., fungi and protists) contain both glucosylceramide (GlcCer) and inositolphosphoceramide (IPC) and their more complex metabolites.…”
mentioning
confidence: 99%
“…Nonetheless, all of these effects of C1P may be cell-type specific, as C1P has also been associated to anti-inflammatory responses (Goggel et al 2004;Hankins et al 2011;Jozefowski et al 2010;Lamour et al 2011). The induction of pro-inflammatory responses by A-SMase-derived ceramides in pulmonary tissue and the inhibition of this enzyme by C1P have gained particular relevance with the recent discovery of a novel C1P transfer protein (CPTP) in human tissues (Simanshu et al 2013). It has been postulated that CPTP could transfer C1P to a site where it exerts an inhibitory effect on sphingomyelin degradation, a situation that is consistent with the reported inhibitory effect of C1P on lysosomal A-SMase (Gomez-Munoz et al 2004) and also with the inhibition of the de novo ceramide synthesis regulatory enzyme serine palmitoyltransferase (Granado et al 2009a), suggesting that these two enzymes may be important anti-inflammatory targets of C1P.…”
Section: Pathophysiological Relevancementioning
confidence: 98%